Motivation to play pump it up: A comparative study of adolescents and adults - Mutiara Amanda Risky; Herman Subarjah; Mohammad Zaky (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2026)
Background. Game-based physical activity (exergaming) has emerged as an innovative approach to promoting physical activity through the integration of digital technology, music, and interactive movement. Objectives. This study examined the motivation of Pump It Up (PIU) players across adolescent and adult age groups, identified dominant motivational factors, and evaluated the potential of PIU as a technology-based exercise alternative. Method. A quantitative comparative descriptive design was employed. Data were collected using an online Likert-scale questionnaire distributed to PIU communities across Indonesia through purposive sampling. Sixty respondents participated, including 14 adolescents (11–20 years) and 46 adults (21–35 years). Data were analyzed using an Independent Samples t-test. Results. Overall motivation was high to very high, with enjoyment emerging as the strongest motivational factor (M = 4.31) in both groups. No significant difference was found in total motivation between adolescents and adults (t = 1.362, p = 0.182). However, adolescents demonstrated significantly higher self-development motivation than adults (t = 2.142, p = 0.040). Conclusion. PIU demonstrates broad motivational appeal across age groups and represents a promising technology-based exercise alternative for promoting physical activity and active lifestyles in Indonesia.